The Re-Evaluation of Function Hall Acoustic Phonetic Condition - Iskandarsyah Siregar (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Phonology is an interdisciplinary science that studies all the mechanical waves in gases, liquids and solids, including vibrations, ultrasound, sound and infrasound. The study of acoustic function is essential nowadays. In conditions of artificial civilization development, complementary electronic ornaments are still very dependent on the level of success with the form of structure and composition of space itself. The problem arises when an adjustment on one side, meant for improvement, shifts the ideal coordinates on the other. For this reason, a comprehensive adjustment and correction idea had to emerge as a solution, with acoustic studies as a starting point. This study tries to describe the ideal pattern design based on investigations and observations of the actual conditions of the Function hall of Building X and tries to determine the suitable material for that space. The stages carried out in the research can be adjusted to the research needs. This step is to get the most comprehensive results with the most effective and efficient steps. Research methods also include integrated software and trial and error analysis. The new pattern design in the Function hall of Building X has good acoustic insulation with some adjustments that still make getting an ideal room evaluation possible.